NKCC2 activity is inhibited by the Bartter's syndrome type 5 gain‐of‐function CaR‐A843E mutant in renal cells. (12th March 2015) - Carmosino, Monica; Gerbino, Andrea; Hendy, Geoffrey N.; Torretta, Silvia; Rizzo, Federica; Debellis, Lucantonio; Procino, Giuseppe; Svelto, Maria
Research article In this report, we describe, for the first time, the direct functional cross‐talk between the calcium sensing receptor (CaR) and the renal NKCC2 co‐transporter in physio‐pathological conditions. Taking advantage of renal cells expressing either the full‐length NKCC2 isoform or a NKCC2 chimeric form, we showed that the constitutively activated CaR‐A853E mutant, causing a Bartter syndrome type 5, significantly decreases NKCC2 phosphorylation at the N‐terminal phospho‐regulatory threonine sites. This effect is mimicked by the expression of the wild‐type CaR maximally activated by both Ca2+ and the positive allosteric modulator R568 and it is likely mediated by arachidonic acid metabolites. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>